ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VII PADA MATERI BILANGAN BULAT - Fajri Wulan Dini; Sri Yunita Ningsih (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study aims to determine the mathematical communication skills of students in integer material in grade VII of SMP Negeri 1 Pasir Penyu. The method used is a descriptive qualitative method in the form of research in the form of a case study. The sample of this study is 30 students. The results of the average score pattern from indicator 1 are high ability level, which is 3, medium is 2.5, and low is 1.67 with a total average of 2.33. From indicator 2, the level of ability is high, which is 3.8, medium is 2.8, and low is 1.23 with a total average of 2.47. From the indicators 3, the level of ability is high, which is 2.8, medium is 1.89, and low is 1.87 with a total average of 2.03. Of the 4 indicators, the level of ability is high, which is 3.8, medium is 2.25 and low is 1.78 with a total average of 2.37. In general, it can be concluded that the mathematical communication skills of students are high, which is 5 people or 16.67%, while 16 people or 53.33%, and low, which is 9 people or 30%.Keywords: Mathematical Communication, Learners.